2010
DOI: 10.1159/000286520
|View full text |Cite
|
Sign up to set email alerts
|

Juxtapapillary Duodenal Diverticula and Pancreatobiliary Disease

Abstract: Juxtapapillary duodenal diverticula (JPD) are observed in around 10–20% of patients undergoing endoscopic retrograde cholangiopancreatography (ERCP). They are acquired extraluminal outpouchings of the duodenal wall through ‘locus minoris resistance’ and their incidence increases with age. They have been studied mainly with regard to their association with pancreatobiliary disease. Choledocholithiasis is considered to be strongly associated with JPD, but the role of JPD in the development of cholecystolithiasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
45
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 32 publications
2
45
0
4
Order By: Relevance
“…[7][8][9][10] Our data indicated the presence of juxtapapillary diverticula as a significant factor for the incidence of OCMRB both at univariate and multivariate analyses, which supports a positive relationship between the presence of juxtapapillary diverticula and papillary dysfunction. The third condition suggested to be related to OCMRB, pneumobilia, is also considered a consequence of dysfunction of the muscle of Oddi.…”
Section: Discussionsupporting
confidence: 73%
“…[7][8][9][10] Our data indicated the presence of juxtapapillary diverticula as a significant factor for the incidence of OCMRB both at univariate and multivariate analyses, which supports a positive relationship between the presence of juxtapapillary diverticula and papillary dysfunction. The third condition suggested to be related to OCMRB, pneumobilia, is also considered a consequence of dysfunction of the muscle of Oddi.…”
Section: Discussionsupporting
confidence: 73%
“…In the elderly, a weakened wall and increased luminal pressure may facilitate outpouching of the duodenal mucosa through the vulnerable spot. 18,19 Pathologic mechanisms through which Lemmel's syndrome is thought to occur include the following. First, diverticulitis or direct mechanical irritation of diverticulum cause distal CBD or ampulla directly compressed mechanically by PAD.…”
Section: Discussionmentioning
confidence: 99%
“…While the association of duodenal diverticula with biliary disease and gallstones is well-documented,8 14 their association with pancreatitis is less clear. There is some evidence that juxtapapillary diverticula are a risk factor for chronic pancreatitis14 and one study by Uomo et al showed that patients with periampullary extraluminal duodenal diverticula were more likely to be diagnosed with idiopathic acute pancreatitis (13.7% vs 1.8% in controls) at endoscopic retrograde cholangiopancreatography 15.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that juxtapapillary diverticula are a risk factor for chronic pancreatitis14 and one study by Uomo et al showed that patients with periampullary extraluminal duodenal diverticula were more likely to be diagnosed with idiopathic acute pancreatitis (13.7% vs 1.8% in controls) at endoscopic retrograde cholangiopancreatography 15. Case reports of acute pancreatitis linked with duodenal diverticula are rare and most involve patients with concurrent congenital abnormality, duodenal tumour or abscess, or with acute on chronic pancreatitis 1618.…”
Section: Discussionmentioning
confidence: 99%